Are Decisions About Household Consumption Always Made With Perfect Knowledge? - Herispon Herispon; Saiful Anuar; Eka Putra (International Journal of Islamic Business and Management Review, 2025)
Description – The economic concept explains that a person is considered to have perfect information and knowledge before or when consuming a product. However, there is no limit on how much information is known about the product. Purpose – This study identifies individuals before or when making consumption decisions regarding a product. Methodology – Using non-probability sampling and purposive sampling methods, sampling technique with mixed questionnaires (online and offline). Using a sample of 422 respondents spread across several regions and cities in Riau Province, using 44 indicators as a reference for product information answered by respondents. Findings – Individual consumption decisions analyzed with the logit probability of reading, caring and knowing information about instant noodles were 0.7599 or 76 percent. Originality/Novelty – This study shows that the information held by individuals in instant noodle consumption can be identified and its size and quantity. Implications – On the other hand, consumption can occur when individuals do not have any information about a product, due to emergency conditions, individual negligence, or being deceived by producers, so individual caution and the role of the government are needed so that consumers are not harmed.